How mobile phone addiction is associated with suicidal ideation in university students in China: Roles of depression and online social support - Hu, Huahua; Yang, Xue; Mo, Phoenix K. H.; Zhao, Chengjia; Kuang, Beibei; Zhang, Guohua; Lin, Guangyao (Frontiers in Psychology, 2022)
Background: Recent studies have highlighted mobile phone addiction (MPA) as a potential risk of suicidal ideation. However, the mechanisms underlying that association require attention. Objective: This investigation aims to examine whether the relationship between MPA and suicidal ideation would be mediated by depression, and buffered by online social support (OSS) in university students. Methods: A total of 1,042 Chinese university students completed the questionnaire including the measures of mobile phone addiction, depression, suicidal ideation, OSS in classroom settings. Results: MPA was positively associated with suicidal ideation through depression (indirect effect =. 23, SE = .02); OSS moderated the association between depression and suicidal ideation (B = − .09, SE= .02, P <.001). Specifically, the effect of depression on suicidal ideation was weaker in individuals with high (versus low) OSS. OSS moderated the association between MPA and suicidal ideation (B = .06, SE= .02, P = .001). The influence of MPA on suicidal ideation was non-significant among individuals with high OSS but negatively significant among students with low OSS. Conclusions: The results enrich the understanding of how MPA may increase suicidal ideation, and highlight the potential importance of reducing depression and enhancing OSS to prevent suicidal ideation in university students.